Empowering Voices: A Three-Year Intervention to Reduce Public Speaking Anxiety among ESL Learners - Pontillas, Marlon S. (South Sulawesi Education Development, 2025)
This paper outlines a structured, research-based intervention program designed to reduce public speaking anxiety among ESL learners at Camarines Sur Polytechnic Colleges and its partner, Zeferino Arroyo High School. Spanning three years, the program consists of three progressive phases: